Corporate Social Responsibility in Chinese and Indian Multinationals - Kubicka, Jolanta (Społeczna odpowiedzialność biznesu w korporacjach chińskich i indyjskich, 2010)
Empirical studies show that there is a positive correlation between socially responsible behaviour and corporate returns. The CSR- is said to be good for society and good for business. The structure and models of CSR in developing countries present a conceptual and practical implication for corporate managers seeking a viable solution to extend their organization's investment in CSR. Research in development of strategies to implement CSR models will be highly useful in the future development of CSR in India and China. With the challenges of globalization, liberalization and the emerging trend towards a free market economy facing India and China, the role of CSR became more and more paramount. The CSR in India evolved from charity and traditional philanthropy (like "infrastructure philanthropy" of Indian Multinational - the Tata Group) towards a more diversified forms of corporate social responsibility (CSR). While the rapid development of the Chinese market brings about more opportunities to implement CSR strategy in many new fields (like "sport philanthropy" of Chinese Multinationals - Haier and SAIC during the Beijing Olimpic Games, the same as "CSR in art or culture" of SAIC and its global joint venture partner GM during Shanghai Expo 2010). Both Chinese and Indian corporations can benefit from adopting corporate responsibility strategies. The development and the implementation of strategies based on international standards and different types and models of corporate social responsibility (CSR) are essential for Chinese - and Indian corporations for further expansion on their home and international markets during the internationalization process. The internationalization process of Chinese and Indian corporations has been increasing the role of corporate social responsibility (CSR) on their home markets, which extended to create positive image and reputation of Chinese and Indian multinationals on foreign markets.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 399-411
Keywords: corporate social responsibility (CSR); Chinese and Indian